Scala Programming Projects : Build real world projects using popular Scala frameworks like Play, Akka, and Spark /: Build real world projects using popular Scala frameworks like Play, Akka, and Spark. (2018) - Valot, Mikaël; Jorand, Nicolas
No abstract available